High-flow priapism in a 12-year-old boy: treatment with super-selective embolization - AR , Mossadeq; R, Sasikumar; Kamarulzaman, Mohd Nazli; Abdullah, M Shafie; Mohd Daud, M Ashraf (Medknow Publications, 2009)
Priapism is caused by an imbalance between penile blood inflow and outflow. There are two types of priapism: low-flow priapism due to venous occlusion and high-flow priapism due to uncontrolled arterial flow to the veins. High-flow priapism most frequently occurs as a result of penile trauma in which the intercavernosal artery disruption causes an arteriocavernosal fistula. It is rarely encountered in the pediatric and prepubertal population. Clinically, it manifests as a painless, prolonged erection after perineal trauma. Treatment ranges from expectant management to open surgical exploration with vessel ligation. We report the successful treatment of high-flow priapism in a 12-year-old prepubertal boy with superselective embolization.